2018
DOI: 10.1371/journal.pone.0199728
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet suppresses the positive effect of creatine supplementation on skeletal muscle function by reducing protein expression of IGF-PI3K-AKT-mTOR pathway

Abstract: High-fat (HF) diets in combination with sedentary lifestyle represent one of the major public health concerns predisposing to obesity and diabetes leading to skeletal muscle atrophy, decreased fiber diameter and muscle mass with accumulation of fat tissue resulting in loss of muscle strength. One strategy to overcome the maleficent effects of HF diet is resistance training, a strategy used to improve muscle mass, reverting the negative effects on obesity-related changes in skeletal muscle. Together with resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…In line with the current results, Ferretti et al [10] reported that Cr supplementation combined with 8 week ladder climbing training increased the phosphorylated AKT and phospho-AKT/total AKT, but had no effect on the mTOR and phospho-mTOR/total mTOR. Aguiar et al [1] investigated the effect of Cr supplementation and 5 weeks of a resistance training program (5 d/wk) on muscle hypertrophy in an animal model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the current results, Ferretti et al [10] reported that Cr supplementation combined with 8 week ladder climbing training increased the phosphorylated AKT and phospho-AKT/total AKT, but had no effect on the mTOR and phospho-mTOR/total mTOR. Aguiar et al [1] investigated the effect of Cr supplementation and 5 weeks of a resistance training program (5 d/wk) on muscle hypertrophy in an animal model.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that amino acid transporter expression following resistance exercise might be linked to mTOR signaling and eIF2α phosphorylation [8]. On the other hand, Cr supplementation in addition to resistance training increases the diameter of skeletal muscle bers by stimulating the expression of insulin-like growth factor-1 (IGF-1) and subsequently activating the AKT-mTOR pathway [10]. Given that both PERK and mTOR are involved in protein synthesis, skeletal muscle mass [23] and satellite cell homeostasis [36], there is limited information regarding the effect of resistance training-induced hypertrophy on PERK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Eshima et al discovered morphological changes of myofiber composition of extensor digitorum longus muscle in HF diet-fed mice for 12 weeks, leading to the impairment of muscle contractile force [17]. Moreover, the mechanisms of skeletal muscle wasting and dysfunction in HF diet-induced obesity are positively correlated among several risk factors and signaling pathways including cardiometabolic risk factors [18], elevating inflammatory factors (such as tumor necrosis factor-α (TNF-α) levels), the activation of oxidative stress [5], autophagy [19,20], and ubiquitin–proteasome pathway [5], the down-regulation of AMPK/PGC-1 [21,22] and IGF/PI3K/Akt/mTOR signaling pathway [21,23], leading to skeletal muscle atrophy and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…A Nikon Eclipse TS100 microscope equipped with a Nikon D5100 digital camera was used to observe and photograph the H&E-stained sections. The cross-section areas (CSA) of individual myofibres were counted and calculated using the image J 1.48 software (National Institutes of Health, Bethesda, MD, USA) in five random fields of each section, as described previously [23,54].…”
Section: Methodsmentioning
confidence: 99%
“…This positive effect of creatine on muscle is probably only observable together with exercise [135,136,137]. Just recently, Ferretti et al [138] demonstrated that during resistance training, Cr monohydrate increases muscle size and performance, suggesting a higher activation of muscle protein synthesis via IGF1-IRS1-PI3K-AKT-mTOR pathway.…”
Section: Nutritional Interventionsmentioning
confidence: 99%